Peran Digital Marketing Sebagai Strategi Dalam Membangun Brand Awareness Pada Toko Kue Browmer Kota Palopo - Claudya Amal Utami; Gusna Aryunita; Ririn Anita; Harmi; Suraidah Sarbia (Jurnal Ekonomi dan Bisnis Digital, 2024)
This journal writing focuses on the role of digital marketing as a strategy in building brand awareness at the Browmer cake shop in Palopo City. The purpose of this writing is to determine the role of digital marketing as a strategy in building brand awareness at the Browmer cake shop in Palopo City. The type of research used is descriptive qualitative research. The data used is secondary data consisting of search results data with research objects, journal articles from research results, previous scientific articles from Google Scholar related to the purpose of writing, namely to determine the role of digital marketing as a strategy in building brand awareness at the Browmer cake shop in Palopo City. The results of the study show that marketing carried out through digital marketing has played a positive role in the sales volume and brand awareness of the Browmer cake shop in Palopo City. This makes it easier for consumers to make product purchases. The ordering process is carried out through personal messages/direct messages on Instagram social media. The Browmer cake shop uses digital marketing not only as a marketing and promotional media, but also as a strategy to build brand awareness in the minds of consumers. Then regarding brand awareness, Browmer's store utilizes Instagram as a social media marketing in conducting brand recall to consumers by utilizing the features available on Instagram to post photos or videos of Browmer's store products every day after production is complete so that consumers can remember Browmer's store products.